Estudo teórico e experimental de secagem de tomate (Lycopersicon esculentum) - Luiz, Marcia Ramos (2012)
Food drying is a process used to ensure the quality and stability of foods, considering that the decrease of water in the material reduces the biological activity and the chemical and physical changes that occur during storage. The objective of this research was to study the heat and mass transfer in drying process of slices of tomatoes and to evaluate the characteristics of drying kinetics in two resistive equipments and a heat pump. The operating conditions for dryers resistive were set at temperatures of 40 and 50 and 60°C with an air velocity of 2.5m/s to the heat pump and a dryer resistive temperature of 55°C and air velocity of 5.7m/s. The experimental results of drying kinetics were represented using mathematical models and are shown in terms of effective diffusivity and convective of the mass. The values found for the effective diffusivity of mass are in agreement with the literature. The convective coefficients mass are the order of 10-1. Those coefficients were not found references in literature. A comparative study between the heat pump and the dryer resistive showed that the first one was more efficient to perform the drying of tomato. We studied the sorption isotherm for tomatoes at temperatures of 50, 60, 70 and 80°C. The results were represented using mathematical models and the GAB model showed the best fit to the experimental data. A numerical study for heat transfer and mass during drying of the product was studied, through the development of a computational code, in configuring an infinite slab. In the modeling process were studied the Fourier Law for heat transfer and Law of Fick for mass transfer. For code validation were used results from the literature and from this present research. The results were satisfactory, but it is necessary to study the variables involved in the drying process for a better adjustment.